PEMBUATAN TAMAN DAN WEBSITE DESA SUKOPURO KECAMATAN JABUNG KABUPATEN MALANG - Dullah, Mohammad; Wardani, Lila Kurnia; Limgiani, Limgiani (Jurnal Difusi Ipteks Legowo, 2024)
The various potentials that exist in the village cannot be seen and accessed using online media so that the various potentials that exist cannot be managed optimally, this is also recognized by the village apparatus where there are no clear road directions (maps) to tourist destinations either based on nature such as Coban and Small and Medium Enterprises (SMEs) in the environment. From the various problems that have been presented, this service focuses on two activities, namely the creation of the Village Website and the Making of the Sukopuro Village Gate Park. The conclusions of the service are 1) The Sukopuro Village website although it is still under repair and continues to be improved, but it can be enjoyed through the desasukopurojabung.com page 2) The Sukopuro Village Gate Garden can already be enjoyed because there are living plants with elegant designs equipped with stones. times and when the night comes the atmosphere becomes bright.